Review of the 25th annual scientific meeting of the International Society for Biological Therapy of Cancer - Jaffee Elizabeth M (Journal of Translational Medicine, 2011)
Abstract Led by key opinion leaders in the field, the 25th Annual Meeting of the International Society for Biological Therapy of Cancer (iSBTc, recently renamed the Society for Immunotherapy of Cancer, SITC) provided a scientific platform for ~500 attendees to exchange cutting-edge information on basic, clinical, and translational research in cancer immunology and immunotherapy. The meeting included keynote addresses on checkpoint blockade in cancer therapy and recent advances in therapeutic vaccination against cancer induced by Human Papilloma Virus 16. Participants from 29 countries interacted through oral presentations, panel discussions, and posters on topics that included dendritic cells and cancer, targeted therapeutics and immunotherapy, innate/adaptive immune interplay in cancer, clinical trial endpoints, vaccine combinations, countering negative regulation, immune cell trafficking to tumor microenvironment, and adoptive T cell transfer. In addition to the 50 oral presentations and >180 posters on these topics, a new SITC/iSBTc initiative to create evidence-based Cancer Immunotherapy Guidelines was announced. The SITC/iSBTc Biomarkers Taskforce announced the release of recommendations on immunotherapy biomarkers and a highly successful symposium on Immuno-Oncology Biomarkers that took place on the campus of the National Institutes of Health (NIH) immediately prior to the Annual Meeting. At the Annual Meeting, the NIH took the opportunity to publicly announce the award of the U01 grant that will fund the Cancer Immunotherapy Trials Network (CITN). In summary, the Annual Meeting gathered clinicians and scientists from academia, industry, and regulatory agencies from around the globe to interact and exchange important scientific advances related to tumor immunobiology and cancer immunotherapy.